Ground-penetrating radar data from Lirung and Langtang Glaciers, Nepal, 2015 - Pritchard, Hamish (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
Ground-penetrating radar (GPR) was used to test glacier ice thickness/glacier bed detectability on debris-covered Himalayan glaciers at a range of frequencies in glacier long- and cross- profiles and at static points. The survey sites were of the Lirung and Langtang Glaciers in the Langtang National Park, Nepal, where debris cover thickness varied from centimetres to several metres. The radar used was the BAS DELORES dipole pulse radar system, operating at 5MHz, 10MHz, 20MHZ and 40MHz. Data were acquired as a stop-go survey at 2-4m intervals on partially snow-covered and entirely debris-covered glacier surfaces in temperatures close to freezing, with a diurnal freeze-thaw cycle.